2022
DOI: 10.1007/s40747-022-00873-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary game analysis of three parties in logistics platforms and freight transportation companies’ behavioral strategies for horizontal collaboration considering vehicle capacity utilization

Abstract: In China, logistics platforms are an effective way to solve vehicle capacity utilization using information sharing. However, most logistics platforms do not possess operational sustainability due to excessive profit-seeking. To address this problem, conflicts of interest among freight transportation participants are discussed using a stakeholder approach. A three-player evolutionary game model (TEGM) is developed to analyze the interactions among freight carriers, freight shippers, and logistics platforms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…For instance, Deng et al developed a three-player evolutionary game model for analyzing the interactions among freight carriers, freight shippers, and logistics platforms. Ten, these researchers analyzed the asymptotic equilibrium and evolutionary stability strategies of the three-player game [6]. Bai et al studied the value cocreation impact mechanism of network freight platforms in the Internet of Tings environment and found that service-dominant logic, transport demand subject participation, and relational embeddedness all promote value cocreation [7].…”
Section: Research On the Behavior Of Carriers Shippers Andmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Deng et al developed a three-player evolutionary game model for analyzing the interactions among freight carriers, freight shippers, and logistics platforms. Ten, these researchers analyzed the asymptotic equilibrium and evolutionary stability strategies of the three-player game [6]. Bai et al studied the value cocreation impact mechanism of network freight platforms in the Internet of Tings environment and found that service-dominant logic, transport demand subject participation, and relational embeddedness all promote value cocreation [7].…”
Section: Research On the Behavior Of Carriers Shippers Andmentioning
confidence: 99%
“…Second, relatively little research has been conducted on the irrational or abnormal behaviors of participants. Most studies assume that all participants in this model are rational individuals who strictly abide by contracts; for instance, Deng et al investigated whether carriers and shippers are willing to share service capabilities and service information [6]. In real life, speculative behavior is likely to occur, and once such speculative behavior occurs, it inevitably afects the behavioral decisions of other participants.…”
Section: Limitations Of the Existing Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has previously underscored the potential of information exchange to enhance information visibility within transportation systems [64]. Furthermore, the process of information exchange serves to eliminate obstructions between disparate systems, align the interests of stakeholders [65], and alleviate unwarranted variations within systems [66].…”
Section: Elaboration Of Experimental Outcomesmentioning
confidence: 99%